A 0.2 V Micro‐Electromechanical Switch Enabled by a Phase Transition. Issue 14 (26th February 2018) - Dong, Kaichen; Choe, Hwan Sung; Wang, Xi; Liu, Huili; Saha, Bivas; Ko, Changhyun; Deng, Yang; Tom, Kyle B.; Lou, Shuai; Wang, Letian; Grigoropoulos, Costas P.; You, Zheng; et al.
Abstract: Micro‐electromechanical (MEM) switches, with advantages such as quasi‐zero leakage current, emerge as attractive candidates for overcoming the physical limits of complementary metal‐oxide semiconductor (CMOS) devices. To practically integrate MEM switches into CMOS circuits, two major challenges must be addressed: sub 1 V operating voltage to match the voltage levels in current circuit systems and being able to deliver at least millions of operating cycles. However, existing sub 1 V mechanical switches are mostly subject to significant body bias and/or limited lifetimes, thus failing to meet both limitations simultaneously. Here 0.2 V MEM switching devices with ≳10 6 safe operating cycles in ambient air are reported, which achieve the lowest operating voltage in mechanical switches without body bias reported to date. The ultralow operating voltage is mainly enabled by the abrupt phase transition of nanolayered vanadium dioxide (VO2 ) slightly above room temperature. The phase‐transition MEM switches open possibilities for sub 1 V hybrid integrated devices/circuits/systems, as well as ultralow power consumption sensors for Internet of Things applications. Abstract : A phase‐transition micro‐electromechanical (MEM) switch is demonstrated with 0.2 V operating voltage and ≳10 6 safe operating cycles in ambient air, which is mainly enabled by the abrupt phase transition of nanolayered vanadium dioxide slightly above room temperature. The phase‐transition MEM switches open possibilities for sub 1 V hybrid integrated devices/circuits/systems, as well as ultralow power consumption sensors for Internet of Things applications.